On the role of the bay of Algeciras in the exchange across the Strait of Gibraltar. - García-Lafuente, Jesús; Sammartino, Simone; Sánchez Garrido, José C.; Naranjo, Cristina (Elsevier, 2019)
The role that the Algeciras Bay, a medium size embayment located in the eastern part of the Strait of Gibraltar, may have on the water exchange through the Strait and on other physical properties of the area has been numerically investigated using different configurations of a numerical model. Three domains have been considered, the present configuration with the Bay and two other configurations in which the Bay is suppressed either by filling the embayment, which produces a longer Strait, or by removing the Gibraltar Rock and isthmus, which gives rise to a shorter Strait. Only little modifications are produced in the mean properties, the shorter Strait increasing very slightly the mean exchange and diminishing the cross-section averaged salinity of the inflow. The spatial pattern of semidiurnal tidal ellipses is changed in the vicinity of the Bay, but other properties such as the minimum amplitude of semidiurnal M2 transport that occurs off the Bay in the Strait and that could be related to the present configuration, remain unaltered. It is speculated that the main consequence of suppressing the Bay relates to the export of primary production, as it acts out as a buffer of water with residence times long enough to sustain high levels of productivity.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/35864
Keywords: Mareas - Algeciras (Bahía, Cádiz); Circulación oceánica - Algeciras (Bahía, Cádiz); Oceanografía - Modelos matemáticos; Tides; Water exchange; Numerical model; Primary production